1981
DOI: 10.1002/1097-0142(19811001)48:7<1590::aid-cncr2820480720>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus profile of hepatocellular carcinoma in the philippines

Abstract: The hepatitis B virus (HBV) profile was investigated in 104 age-grouped hepatocellular carcinoma (HCC) patients and 84 controls from the Philippines. The HCC-control percent positivities of the HBV parameters are: HBsAg: 70-18; anti-HBs: 25-37; anti-HBs: 25-37; anti-HBc: 94-35; HBeAg: 5-2; anti-HBe: 60-30; HBV exposure rate: 97-57; current infection: 80-31. Male HCC anti-HBs positivity is significantly lower than in controls. Female HCC patients' anti-HBs are also lower than controls, but this difference is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 21 publications
5
3
0
Order By: Relevance
“…Thirty-six, or 97.396, of our patients with HCC had anti-HBc in their serum, 22 of these in a high concentration of over lo3. Similar result$ have been reported from the Philippines (94%; controls, 37%) (12) and from South Africa (89%; controls, 37.5%) (14). The high concentration of anti-HBc is taken as a sign of active replication of hepatitis B virus (HBV).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Thirty-six, or 97.396, of our patients with HCC had anti-HBc in their serum, 22 of these in a high concentration of over lo3. Similar result$ have been reported from the Philippines (94%; controls, 37%) (12) and from South Africa (89%; controls, 37.5%) (14). The high concentration of anti-HBc is taken as a sign of active replication of hepatitis B virus (HBV).…”
Section: Discussionsupporting
confidence: 77%
“…The anti-HBs positivity of 53.9% of the HBsAg-negative cases is of the same magnitude as that of other series from regions with a high incidence of H C C (11,12). It is similar to (12) or somewhat lower than (12,14) that found in control materials.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…There are conflicting reports in the literature concerning the relative frequency of HBeAg among HBsAg-positive HCC cases and HBsAg-positive healthy controls; some authors report higher frequency among HBsAg-positive HCC cases (Lingao et al, 1981;Chung et al, 1983;Kew et al, 1984), and some report higher frequency among HBsAg-positive controls (Chu et al, 1983;Musca et al, 1983;Liaw et al, 1984;Kim et al, 1985), whereas others find no remarkable or statistically significant differences between the two groups . In the present study serum HBeAg was found in a higher proportion among HBsAg-positive HCC cases than among HBsAg-positive controls; the finding is intriguing since it is the ''latent'' anti-HBe-related type of HBV infection which is more frequently associated with hepatocarcinogenesis (Maupas et al, 1977;Chu et al, 1983;Musca et al, 1983;Shafritz and Hadziyannis, 1984).…”
Section: Discussionmentioning
confidence: 99%